Crisis of Survival of Thermal Power Plants in India due to Consistently Falling Capacity Utilization – Factors Responsible and Future Outlook - Tripathi, Alok K. (International Journal of Energy Economics and Policy, 2021)
Thermal power plants in India are facing unprecedented crisis. Their capacity utilization (known as Plant Load Factor, PLF) has been consistently falling over the years. In the year 2019-20 the national average PLF stood at 55.4%, down from 78.6 % in 2007-08. It is predicted that the national average PLF may fall to 48% by 2022. Many new thermal power plants, set up with substantial capital investment are staring at a bleak future. It is an irony that on one hand, the country is power deficit and on the other hand, a large amount of new, efficient and low-carbon- footprint thermal power remains grossly unutilised. Since considerable investment has gone into these thermal power assets, the falling PLF is a matter of concern for all the key stakeholders including the power producers, lenders, regulators and consumers. This paper identifies eleven major factors responsible for this situation and discusses future outlook of these factors. We find that urgent review and halt on fresh thermal capacity addition, immediate phasing out of old inefficient plants and policy support to enable flexible operation of the thermal power generators are imperative to save the sector from imminent collapse. Keywords: Thermal Power, Energy Economics, Plant Load Factor, Coal, Renewable, Flexible Operation JEL Classifications: Q40, Q42, Q43, Q48 DOI: https://doi.org/10.32479/ijeep.10965